Explaining differences in efficiency among farrow-to-finish producers - Rowland, W.W.; Langemeier, Michael R.; Featherstone, Allen M.; Schurle, Bryan W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To remain competitive, hog operations will need to continue to improve production efficiency and manage costs. Kansas Farm Management Association data from 1992 to 1994 were used to measure technical, economic, and overall efficiency for 43 farrow-to-finish operations in Kansas. On average, the farms had .89 technical, .75 economic, and .67 overall efficiencies. Efficiency was related positively to the number of litters produced and pounds of pork produced per litter. Efficiency was related negatively to percentage of labor hired, feed conversion rates, and capital investment per litter. Pounds of pork produced per litter and feed conversion had the largest impacts on efficiency. Results suggest that increasing the pounds of pork produced per litter or decreasing feed conversion would have a sizable impact on technical, economic, and overall efficiency.
Keywords: Swine; Efficiency; Profitability